Evaluation the Expression Level of miRNA 155 in Whole Blood as A New Biomarker in the Patients Diagnosed with Alopecia Areata - Alfadul, Sajjad M.; Obaid, Khmaeel M.; Alnomani, Yaqdhan T. (Medical Science Journal for Advance Research, 2025)
Background: Alopecia areata (AA) is a particular type of autoimmune skin illness that causes hair follicles to burst, resulting in abrupt, patchy hair loss that leaves no scars. In rare cases, it may develop to lose hair on the all body (alopecia universalis) or only the hair of the scalp (alopecia totalis). MiRNAs are little non-coding RNAs, approximately less or more than 22 nucleotides in length, and their abnormal function or expression has been involved in many autoimmune diseases. The causes of alopecia areata are not clear yet. Aim: To evaluate the level of miR-155 in whole blood in alopecia areata patients and correlate it with certain clinical variables. Material and methods: miR-155 levels in 40 alopecia areata patients and 40 healthy controls were assessed by using real-time PCR. Results: In comparison to healthy control, the levels of miRNA-155 in the alopecia areata patients differed in a statistically significant way (P < 0.001). There was a negative association between miR-155a and some clinical variables. Conclusion: The pathogenesis of alopecia areata seems to be significantly affected by miR-155.